A new species of Metzia (Cypriniformes: Cyprinidae) from Northern Laos - Shibukawa, Koichi; Phousavanh, Phouvin; Phongsa, Koneuma; Iwata, Akihisa (Zootaxa, 2012)
A new cyprinid fish, Metzia bounthobi, is described on the basis of 18 specimens (including 10 specimens in type series)from the Mekong River basin in Phongsaly and Luang Prabang Provinces, northern Laos. The species is distinguishedfrom congeners by having the following diagnostic traits: 18–20 branched anal-fin rays (vs. 10–18 in the others); 49–55lateral-line scale rows (vs. 35–48); 33–36 predorsal scale rows (vs. 15–20); 20–22 circumpeduncular scale rows (vs.14–18); 8–10 gill rakers on outer surface of first gill arch (vs. 12–18). The new species also resembles species of Hemic-ulterella, Ischikauia and at least some species of Anabarilius, in sharing a sharp keel developed only between the base ofthe pelvic fin and anus, soft last unbranched dorsal-fin ray, and air bladder composed of two chambers; however, M.bounthobi differs in having a considerably rounded snout (vs. pointed in Hemiculterella, Ischikauia and Anabarilius),18–20 branched anal-fin rays (vs. 8–17 in Hemiculterella, Ischiakuia and Anabarilius), 49–55 lateral-line scale rows (vs.more than 58 in Ischikauia and Anabarilius, except for A. transmontana with 54–57), air bladder with rounded posteriorend (vs. posterior end with a small lobe at least in Hemiculterella) and 39–40 vertebrae (vs. 40–43, 42–43 and 43–48 in Hemiculterella, Ischikauia and Anabarilius, respectively).